2019
DOI: 10.1037/stl0000129
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-experimental and experimental assessment of electronic textbook experiences: Student perceptions and test performance.

Abstract: An increasing number of psychology students encounter electronic textbooks (e-texts), whether by personal choice or instructor adoption. Across two studies-one quasiexperimental and one experimental-we compared students' experiences with print books versus e-texts. Study 1 capitalized on a naturally occurring comparison: the same course was taught across consecutive semesters at the same university using the same text, but once requiring a print book and once requiring an e-text. An anonymous survey revealed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…A review of the findings to consider which features were beneficial and which were not helpful would help in understanding these findings. There were 17 studies in which statistically significant positive effects on at least one learning measure were noted (Asrowi et al, 2019;Chang et al, 2019;Chaudhri et al, 2013;Chen et al, 2014;Chen et al, 2018;Dennis et al, 2016, Ebied 2015Jin, 2013;Hsiao et al, 2016;Jin, 2013;Li et al, 2013;Lustria, 2007;Mochizuki et al, 2019;Sommers et al, 2019;Zarzour & Sellami, 2017;Zarzour & Sellami, 2018a;Zarzour & Sellami, 2018b). Most of these studies with positive effects had multiple interactive features making it challenging to discern the features or combination of features most effective.…”
Section: E-text Interactive Features 13mentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the findings to consider which features were beneficial and which were not helpful would help in understanding these findings. There were 17 studies in which statistically significant positive effects on at least one learning measure were noted (Asrowi et al, 2019;Chang et al, 2019;Chaudhri et al, 2013;Chen et al, 2014;Chen et al, 2018;Dennis et al, 2016, Ebied 2015Jin, 2013;Hsiao et al, 2016;Jin, 2013;Li et al, 2013;Lustria, 2007;Mochizuki et al, 2019;Sommers et al, 2019;Zarzour & Sellami, 2017;Zarzour & Sellami, 2018a;Zarzour & Sellami, 2018b). Most of these studies with positive effects had multiple interactive features making it challenging to discern the features or combination of features most effective.…”
Section: E-text Interactive Features 13mentioning
confidence: 99%
“…Questions or other assessments with feedback were considered to be particularly helpful as they could guide the reader to make accurate connections thereby promoting better textbase and situation model development. Five of the studies with positive effects involved some form of questions or prompts with feedback (Asrowi et al, 2019;Chaudhri et al, 2013;Chen et al, 2018;Hsiao et al 2016;Sommers et al, 2019). However, there were some exceptions.…”
Section: E-text Interactive Features 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the absence of strict limitations on the part of the authorities as to the choice of online tools (or web applications) when teaching, all kinds of means and digital technologies have come to the disposal of teachers, with the help of which everything that was only dreamed of a few years ago has become real. In this connection, it became relevant to operate with the concept of "electronic textbook" (e-textbook) (Sommers, Shin, Greenebaum, Merker & Sanders, 2019;Leddo, J. et al, 2020). However, many scholars talked about a modern and actual e-textbook as "interactive textbook" (Van Horne, Russell & Schun, 2016), "interactive digital textbook" (Bikowski, & Casal, 2018) and "intelligent e-textbook" (Weber & Brusilovsky, 2015;Boulanger & Kumar, 2021) highlighting their various features in different ways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, interactive e-texts often provide readers with repeated practice testing opportunities followed by instant feedback, as well as videos that illustrate concepts, digital glossaries that show the definition of terms, and figures and tables that lend themselves to active user manipulation (Clinton-Lisell et al, 2021;Spencer et al, 2020). Indeed, several previous studies have found no evidence for poorer student performance in interactive e-text conditions compared to print conditions (Almekhlafi, 2021;Liu et al, 2020;Morris & Lambe, 2017;Sommers et al, 2019), and yet others have found better performance with interactive e-texts (Asrowi et al, 2019;Chaudhri et al, 2013;Dennis et al, 2016;Hsiao et al, 2016). Moreover, a recent meta-analysis that included only studies involving interactive e-texts showed an advantage of e-texts over print text on learning outcomes (Clinton-Lisell et al, 2021).…”
mentioning
confidence: 99%